One-pot synthesis of redispersible polymer-stabilized ZnO nanocomposites - Buenviaje, Salvador C. Jr.; Edañol, Yasmin D.G.; Legaspi, Enrico Daniel R.; Payawan, Leon M. Jr.; Usman, Ken Aldren S. (2021)
"Nanomaterials have gained noteworthy attention in several applications due to their significantly improved properties relative to their bulk counterparts. However, achieving effective redispersibility of nanomaetrials in a wide array of solvents, with inhibited particle agglomeration and preserved properties such as large surface areas, remains challenging. In this study, a method of imparting both redispersibility and colloidal stability into zinc oxide (ZnO) nanoparticles was done through in situ addition of polymer stabilizers such as poly(acrylic acid) (PAA), poly(ethylene glycol) (PEG), and poly(vinylpyrrolidone) (PVP)" - title page.
Includes bibliographical references.
Keywords: Dispersion; Polyethylene glycol; Zinc oxide